Thyroglobulin Antibodies are Associated with Symptom Burden in Patients with Hashimoto's Thyroiditis: A Cross-Sectional Study - Barić, Ana; Brčić, Luka; Gračan, Sanda; Škrabić, Veselin; Brekalo, Marko; Šimunac, Marta; Lovrić, Vesela Torlak; Anić, Iva; Barbalić, Maja; Zemunik, Tatijana; Punda, Ante; Boraska Perica, Vesna (Immunological investigations, 2019)
Background: Hashimoto's thyroiditis (HT) is the most common form of autoimmune thyroid disorders characterized by lower production of thyroid hormones and positivity to autoantibodies to thyroglobulin (TgAb) and/or thyroid peroxidase (TPOAb). We performed a comprehensive phenotypic characterization of patients with HT, with specific focus on thyroid autoimmunity, to get better understanding of disease manifestation. Methods: We collected information on thyroid-specific phenotypes (TSH, T3, T4, fT4, TgAb, TPOAb, thyroid volume) and other clinical phenotypes (age, body surface area, number of hypothyroidism symptoms, blood pressure) from 290 patients with HT without levothyroxine (LT4) therapy with the aim to test for correlations between thyroid-specific and clinical phenotypes. Results: Our key and novel finding is the existence of significant positive correlation between TgAb levels and the number of symptoms (r = 0.25, p = 0.0001) in HT patients without LT4 therapy that remained significant after adjustment for TPOAb, T3, TSH levels and thyroid volume (β = 0.66, SE = 0.3, p = 0.0299). Increased TgAb levels are significantly associated with fragile hair (p = 0.0043), face edema (p = 0.0061), edema of the eyes (p = 0.0293) and harsh voice (p = 0.0349). Conclusions: Elevated TgAb levels are associated with symptom burden in HT patients, suggesting a role of thyroid autoimmunity in clinical manifestations of HT. Based on these results, we recommend screening for TgAb antibodies in HT patients with symptom burden. We also suggest that further work on understandings of symptoms appearance due to their autoimmune or hypothyroid causation is needed.